Kenyon L. Butterfield papers - Butterfield, Kenyon L. (Kenyon Leech), 1868-1935.
Correspondence, memoranda, diaries, speeches, writings, articles, studies, surveys, printed matter, photographs, and other papers relating to Butterfield's work with the American Country Life Association, U.S. Country Life Commission, and foreign Christian missions. Also documents his innovations in the administration, curricula, and services of agricultural colleges. Correspondents include Ray Stannard Baker, Calvin Coolidge, H. Paul Douglass, Charles W. Garfield, William Ernest Hocking, Cyrus Hall McCormick, Walter Hines Page, Franklin D. Roosevelt, William Howard Taft, Henry A. Wallace, Henry Cantwell Wallace, and members of the Butterfield family.
Agronomist and college administrator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Baker, Ray Stannard, -- 1870-1946 -- Correspondence; Coolidge, Calvin, -- 1872-1933 -- Correspondence; Douglass, H. Paul -- 1871-1953 -- Correspondence; Garfield, Charles W. -- 1848-1934 -- Correspondence; Hocking, William Ernest, -- 1873-1966 -- Correspondence; McCormick, Cyrus Hall, -- 1859-1936 -- Correspondence; Page, Walter Hines, -- 1855-1918 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Wallace, Henry A. -- 1888-1965 -- Correspondence; Wallace, Henry Cantwell, -- 1866-1924 -- Correspondence; Butterfield family -- Correspondence; United States. -- Country Life Commission; American Country Life Association; Agricultural colleges -- United States; Agricultural education -- United States; Country life -- United States; United States -- Rural conditions; Missions; Agronomists; College administrators